Karakteristik Campuran Laston Lapis Antara Menggunakan Abu Jerami Sebagai Bahan Substitusi Filler - Agnis Irman E. Pakka; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2021)
This study aims to determine the characteristics the mixture of intermediate layers using straw ash as a substitute for cement filler. The method in this research is to test the characteristics of the straw ash, then design the composition of the intermediate lastton mix, as well as the marshall test to obtain the characteristics of the intermediate layer of lastton using straw ash as a cement filler substitution. Where the ash content of straw used as a substitute for cement filler is 0%, 25%, 50%, 75%, and 100% of the weight of cement filler. The results showed that the stability, Flow, VIM, VMA, and VFB at 0%, 25%, 50% straw ash content met the 2018 bina marga specifications, while VMA at 75% straw ash content did not meet the 2018 bina marga specifications, and VMA, VFB at 100% straw ash content also does not meet the 2018 bina marga specifications.